1985
DOI: 10.1002/jcp.1041240224
|View full text |Cite
|
Sign up to set email alerts
|

Induction of DNA polymerase α in senescent cultures of normal and Werner's syndrome cultured skin fibroblasts

Abstract: DNA polymerase alpha activity was determined following serum stimulation of early and late passages of human diploid fibroblast-like (HDFL) cultures derived from apparently normal donors (two strains) and from a patient with Werner's syndrome (one strain). Induction of this enzyme was observed in both low passage, actively proliferating cultures and in postmitotic "senescent" cultures from all three strains. The maximal polymerase activity of early and late passage cells of each strain were nearly identical wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Using a uniform set of procedures, we find that the inhibitors from senescent HDF, density-inhibited quiescent HDF, and serum-deprived quiescent HDF all have (i) the same dose response curves; (ii) the same sensitivity to trypsin, heat, and periodate; and (iii) the same inability to inhibit SV40-transformed HDF. These results support the Recent reports from several laboratories (27)(28)(29) have shown that senescent HDF (defined here as cells with >90% life-span completed) can carry out a number of events in the prereplicative pathway from Go to S phase, even though only a small fraction of the cells can initiate DNA synthesis. Rittling et al (27) studied 11 cell-cycle-dependent genes, including the late G1/S phase genes thymidine kinase and histone H3, and found that each one was expressed in serum-stimulated senescent HDF at levels comparable to those in serum-stimulated quiescent young HDF.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Using a uniform set of procedures, we find that the inhibitors from senescent HDF, density-inhibited quiescent HDF, and serum-deprived quiescent HDF all have (i) the same dose response curves; (ii) the same sensitivity to trypsin, heat, and periodate; and (iii) the same inability to inhibit SV40-transformed HDF. These results support the Recent reports from several laboratories (27)(28)(29) have shown that senescent HDF (defined here as cells with >90% life-span completed) can carry out a number of events in the prereplicative pathway from Go to S phase, even though only a small fraction of the cells can initiate DNA synthesis. Rittling et al (27) studied 11 cell-cycle-dependent genes, including the late G1/S phase genes thymidine kinase and histone H3, and found that each one was expressed in serum-stimulated senescent HDF at levels comparable to those in serum-stimulated quiescent young HDF.…”
Section: Discussionsupporting
confidence: 90%
“…The data presented in this paper show that abolition of the inhibitor in response to serum stimulation is an event that is increasingly defective in old HDF and absent in fully senescent HDF. Therefore, we suggest that abolition of the inhibitor is on a different pathway of response to serum stimulation than are the prereplicative events studied by Rittling et al (27), Olashaw et al (28), and Pendergrass et al (29). An alternative possibility is that abolition of the inhibitor is on the same pathway as induction of DNA polymerase a, thymidine kinase, and histone mRNA synthesis, but it occurs at a later time, which would have to be just at the G1/S border.…”
Section: Discussionmentioning
confidence: 65%
“…Our results are not inconsistent with such data but indicate that such an inhibitor does not block the progression of senescent cells to the S phase. Furthermore, Pendergrass et al (50) show that the levels of DNA polymerase activity in senescent cells is similar to that in young cells. This is another example of an S-phase gene product whose levels are undiminished in noncycling, senescent cells.…”
Section: Discussionmentioning
confidence: 97%
“…thymidine kinase and Histone H3 (Rittling et al, 1986). Thymidine kinase (Cristofalo, 1973) and DNA polymerase (Pendergrass et al, 1985) enzyme activities have also been shown to be unaltered in senescent cells. It is therefore of considerable interest that Ki-67, a proliferation-associated antigen (Gerdes et al, 1983) is not inducible by growth factors in phase III cells.…”
Section: Discussionmentioning
confidence: 99%